Văn học Việt Nam thế kỷ XX : Truyện ngắn 1945-1975. - Phan Cự Đệ; Bùi Việt Thắng; Hà Văn Đức; Lý Hoài Thu; Hồ Thu Giang; Nguyễn Thị Hương Giang (Văn học, 2004)
Nguyên Ngọc; Mai Ngữ; Đinh Quang Nhã; Hồ Phương; Nguyễn Thế Phương; Dương Thị Xuân Quý; Nguyễn Quang Sáng.